Investigating the possible impact of peritoneal tumor exposure amongst women with early stage cervical cancer treated with minimally invasive approach. Issue 5 (May 2021) - Pedone Anchora, Luigi; Bizzarri, Nicolò; Kucukmetin, Ali; Turco, Luigi Carlo; Gallotta, Valerio; Carbone, Vittoria; Rundle, Stuart; Ratnavelu, Nithya; Cosentino, Francesco; Chiantera, Vito; Fagotti, Anna; Fedele, Camilla; et al.
Abstract: Introduction: Recent findings show a detrimental impact of the minimally invasive approach on patients with early stage cervical cancer (ECC). Reasons beyond these results are unclear. The aim of the present article is to investigate the possible role of peritoneal contamination during intracorporeal colpotomy. Methods: patients with early stage cervical cancer were divided into 2 groups: no intraperitoneal exposure (N-IPE) intraperitoneal exposure (IPE) during minimally invasive surgery. Patients of the 2 groups were propensity-matched according to the major risk factors. Results: 226 cases of the IPE group had a significant worst prognosis than the 142 cases of the N-IPE group (4.5-years disease free survival: 86.6% vs 95.9% respectively, p = 0.005), while N-IPE had similar survival to open surgery (4.5-years disease free survival: 95.0% vs 90.5% respectively, p = 0.164). Distant recurrence was more frequent among IPE patients with a borderline significance (3.5% vs 0.4% among IPE and N-IPE respectively, p = 0.083). On multivariate analysis, intraperitoneal tumor exposure was an independent prognostic factors for worse survival; patients belonging to the N-IPE group had a risk of recurrence of about 3-fold lower compared to patients of the IPE group (hazard ratio: 0.37, 95% confidence interval: 0.15–0.88, p = 0.025). Conclusion: it would be advisable that further prospective studies investigating the efficacy of different surgical approach in ECC take into consideration of this issue. Moreover, all other measures that could potentially prevent peritoneal exposure of tumor should be adopted during minimally invasive surgery for early stage cervical cancer to provide higher survival outcomes. Highlights: ∙ Minimally invasive surgery showed a detrimental oncological effect only in the subset of cervical cancer. ∙ The particular grow of cervical cancer could be connected with a higher probability of tumor spread during colpotomy. ∙ Tumor peritoneal contamination could explain worse outcomes of minimally invasive in respect to open surgery.